Under pressure? Single parents in the UK - Klett-Davies, Martina (Gütersloh, 2016)
"For children in single parent families, the risk of living in income poverty is extremely high and the demands on single parents are increasing. Therefore, the situation of single parents and their children requires urgent attention.